PENGARUH PENGGUNAAN DIGITAL MARKETING DAN KEMUDAHAN AKSES LAYANAN APLIKASI BELANJA ONLINE DALAM PENINGKATAN DAYA BELI MASYARAKAT KOTA MEDAN DI ERA REVOLUSI INDUSTRI MARKETING 4.0 - Mila Yulia Herosian; Made Adhiguna Samvara (Jurnal Akrab Juara, 2019)
This research is based on the theory of Marketing Management science related to the development of the digital economy in modern global-based platform organizations as one of the applications that accelerates and facilitates the use of online shopping application services in Indonesia. This research method uses a quantitative descriptive approach with the nature of the research is explanatory. The population in this study is the number of digital marketing service users by 120,856 respondents and the sampling technique using the Slovin formula obtained as many as 100 respondents used in this study. The results obtained in this study are that partially the use of digital marketing obtained tcount > ttable (1,588 > 1,290) and easy access to services obtained tcount > ttable (1,434 > 1,290) has a significant positive effect > 0.10 in increasing people's purchasing power Medan city, while simultaneous use of digital marketing and the ease of access of services obtained the value of Fcount> Ftable (2.337 > 2.36) has a positive and not significant effect on increasing the purchasing power of the people of Medan City in the era of the marketing industry revolution 4.0